A scale to measure attitude of trainers towards facilitation - Barman, U.; Kumar, B. (2009)
Training plays an important role in human resources development. To make a training programme effective trainer must act as a facilitator. To become a facilitator, trainer should have a favourable attitude towards facilitation. So it is important to know the trainer's attitude towards facilitation. Therefore, an attempt has been made to develop a scale to measure the attitude of trainer's towards facilitation. In the present study, 15, situations related with different training style were considered in the scale to measure the attitude. Reproduced.
Keywords: Training